ACE Gene I/D Polymorphism and Acute Pulmonary Embolism in COVID19 Pneumonia: A Potential Predisposing Role - Calabrese, Cecilia; Annunziata, Anna; Coppola, Antonietta; Pafundi, Pia Clara; Guarino, Salvatore; Di Spirito, Valentina; Maddaloni, Valeria; Pepe, Nicola; Fiorentino, Giuseppe (Frontiers in Medicine, 2021)
Most recent studies have stressed a high risk of thromboembolism in patients with SARS-CoV-2 infection, particularly in those with severe COVID-19 pneumonia. Counterbalance between angiotensin-converting-enzyme (ACE) and ACE2 activities in COVID-19 disease may be crucially involved in the thrombo-inflammatory process. Currently, no study has investigated ACE I/D polymorphism involvement in COVID-19 disease complicated by pulmonary embolism, hence the aim of the present pilot study. This is a retrospective, single-center observational case-control study, conducted at the Sub-Intensive Care Unit of A.O.R.N. Ospedali dei Colli, Cotugno Hospital, Naples (Italy). We included 68 subjects with severe/critical COVID-19 pneumonia. COVID-19 patients were divided according to occurrence of PE (PE+, n=25) or absence of thromboembolic complications (PE–, n=43). Assessment of ACE I/D polymorphisms showed a statistically significant difference between PE+ and PE- patients (p=0.029). Particularly, prevalence of D/D homozygous polymorphism was significantly higher in PE+ COVID-19 patients than in PE– (72% vs. 46.5%; p=0.048), while heterozygote I/D polymorphism was significantly lower expressed in PE+ patients than in PE– (16% vs. 48.8%; p=0.009). Computed tomographic pulmonary angiography showed predominantly mono/bilateral sub-segmental embolisms. In conclusion, our findings let us hypothesize a genetic susceptibility to thromboembolism in COVID-19 disease. ACE D/D polymorphism might represent a genetic risk factor, although studies on larger populations are needed.